2012
DOI: 10.5740/jaoacint.sge_paradowska
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Drug Active Ingredients by Chemometric Processing of Solid-State NMR Spectrometry Data—The Case of Acetaminophen

Abstract: This paper presents a preliminary study in building discriminant models from solid-state NMR spectrometry data to detect the presence of acetaminophen in over-the-counter pharmaceutical formulations. The dataset, containing 11 spectra of pure substances and 21 spectra of various formulations, was processed by partial least squares discriminant analysis (PLS-DA). The model found coped with the discrimination, and its quality parameters were acceptable. It was found that standard normal variate preprocessing had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
1
0
Order By: Relevance
“…Two of these studies, employing XRPD and DSC, respectively, have been developed by the group of Komsta [53,54]. The third set of models was built from ssNMR spectroscopic data, with the aim to detect the presence of acetaminophen in over-the-counter pharmaceutical formulations [55].…”
Section: Identification Of Active Pharmaceutical Ingredients At the S...mentioning
confidence: 99%
“…Two of these studies, employing XRPD and DSC, respectively, have been developed by the group of Komsta [53,54]. The third set of models was built from ssNMR spectroscopic data, with the aim to detect the presence of acetaminophen in over-the-counter pharmaceutical formulations [55].…”
Section: Identification Of Active Pharmaceutical Ingredients At the S...mentioning
confidence: 99%
“…[20][21][22][23] A chemometric technique was also used for the determination of PARA. 24 Few methods have been reported for the simultaneous determination of PARA and PAP, including spectrophotometry, 25 electrochemical determination, 26 and using sequential injection analysis. 27 A literature survey revealed that few methods were reported for the determination of PAMB, including spectrophotometry, 28,29 and HPTLC.…”
Section: Introductionmentioning
confidence: 99%